Single nucleotide polymorphism array analysis of bone marrow failure patients reveals characteristic patterns of genetic changes. (14th October 2013) - Babushok, Daria V.; Xie, Hongbo M.; Roth, Jacquelyn J.; Perdigones, Nieves; Olson, Timothy S.; Cockroft, Joshua D.; Gai, Xiaowu; Perin, Juan C.; Li, Yimei; Paessler, Michele E.; Hakonarson, Hakon; Podsakoff, Gregory M.; et al.
Summary The bone marrow failure syndromes (BMFS) are a heterogeneous group of rare blood disorders characterized by inadequate haematopoiesis, clonal evolution, and increased risk of leukaemia. Single nucleotide polymorphism arrays (SNP‐A) have been proposed as a tool for surveillance of clonal evolution in BMFS. To better understand the natural history of BMFS and to assess the clinical utility of SNP‐A in these disorders, we analysed 124 SNP‐A from a comprehensively characterized cohort of 91 patients at our BMFS centre. SNP‐A were correlated with medical histories, haematopathology, cytogenetic and molecular data. To assess clonal evolution, longitudinal analysis of SNP‐A was performed in 25 patients. We found that acquired copy number‐neutral loss of heterozygosity (CN‐LOH) was significantly more frequent in acquired aplastic anaemia (aAA) than in other BMFS (odds ratio 12·2, P < 0·01). Homozygosity by descent was most common in congenital BMFS, frequently unmasking autosomal recessive mutations. Copy number variants (CNVs) were frequently polymorphic, and we identified CNVs enriched in neutropenia and aAA. Our results suggest that acquired CN‐LOH is a general phenomenon in aAA that is probably mechanistically and prognostically distinct from typical CN‐LOH of myeloid malignancies. Our analysis of clinical utility of SNP‐A shows the highest yield of detecting new clonal haematopoiesis at diagnosis and at relapse.